Combined multi-attribute inpatient thermal comfort requirements in hospitals: A designer's assessment method. (October 2021) - Alotaibi, Badr S.; Codinhoto, Ricardo; Albadra, Dima; Lo, Stephen
Abstract: Thermal comfort within healthcare buildings has a significant impact on health. If buildings are not adequately designed, variations in hygrothermal can increase morbidity and lead to death. Thus, incorporating various thermal comfort solutions within building design is paramount, and there are various tools that can assist the design of thermal comfort in buildings. However, these tools (and standards) fail to address design trade-offs sufficiently, account for different aspects of the thermal environment within regular patient rooms or consider inpatients' varied medical conditions and complex underlying factors. To fill these gaps, this research proposes a H ospital E nvironmental A ppraisal T hermal comfort (HEAT) evidence-based design tool. The methods to develop the tool include a systematic literature review, tool design and double validation via a survey questionnaire and interviews with healthcare building designers. HEAT contains eight statements, followed by several evidence-based design recommendations, that address key areas such as design flexibility, coordination, adaptation, activity level, shading, monitoring and airstream. HEAT features three appraisal variants based on a scoring system for statements ranging from general to specific and provides designers with essential information to evaluate and improve design proposals at various design stages. HEAT advances currently available healthcare design tools by providing additional functionality relating to indoor environmental comfort. Thus, this tool would have practical and theoretical implications. Highlights: Current healthcare design tools do not support design of thermo-flexible spaces. Producing an evidence-based tool to complement the shortage of existing tools. Eight design domains are created based on patient thermal comfort demands. Flexible scoring approaches to use within the design process cycle.